ABOUT THE UNLIMITATION STATUTE ON APPEAL AGAINST LEVY OF EXECUTION BASED ON UNFAIR TERMS - Mirel-Emanuel NEACȘU (Challenges of the Knowledge Society)
This paper aims to clarify the implications of the latest amendments made by the Romanian legislator in the field of unfair terms relating to the exercise of the right to appeal against levy of execution in Romanian civil law. These, far from being unambiguous, are to be explained from the perspective of the effects produced, with the main focus on the time limit for exercising the appeal. Once these effects have been determined, we will verify whether the rights and interests of sellers or suppliers are not disproportionately affected, whether there were no other legal solutions that the legislator could have implemented and, in any case, whether the changes in the relevant legislation are beneficial or not. Research methods will be based on a systemic interpretation of civil law provisions as well as rules of Union law. It is also important to identify and analyze the relevant doctrine and, perhaps the most difficult thing to do, to find the link between the autonomous concepts used by the CJEU, the political-jurisdictional authority of the EU, and the concepts of national law. The case-law of the Romanian courts is also particularly relevant and we will try to indicate, sufficiently and where appropriate, such decisions. We believe that clarifying the above-mentioned aspects is particularly important and must be done as quickly as possible, as it is necessary to eliminate the non-unitary practices in this area, practices which lead to an undesirable lack of predictability and predictability for both professionals and consumers.